A bibliometric overview of the Journal of Hospitality and Tourism Management: Research contributions and influence. (June 2021) - Sigala, Marianna; Kumar, Satish; Donthu, Naveen; Sureka, Riya; Joshi, Yatish
Abstract: The Journal of Hospitality and Tourism Management (JHTM) has been growing from strength to strength, and it is currently widely recognized as one of the top ranked journals in its own field. This study represents a first attempt to provide a comprehensive overview of JHTM publications from 2006 to 2020 in order to identify the research developments and trends that signify the evolution of the journal's research contributions and influence. To achieve that, several bibliographic indicators are used such as, bibliographic coupling analysis, co-authorship analysis and keyword co-occurrence. Overall, in line with the journal's impact factors and rankings, the bibliometric analyses confirm the increasing research contribution and influence of the journal in terms of quantity and quality of research outputs. Thematic analyses findings reveal that the JHTM has continuously published articles focusing on original and contemporary topics including: tourism experiences, service quality, hospitality management skills, work-family conflict, sustainability and responsible tourism. Overall, the findings provide meaningful insights to help the JHTM editorial board and the scholarly community alike to formulate research agendas and inform research strategies that can help them to make a significant and influential contribution to the scientific field.